A method for obtaining the OI value of a water-based graphite negative electrode sheet and a method for screening graphite materials
By directly testing the OI value of the oil-based negative electrode sheet, the problem of inaccurate determination of the OI value of the water-based negative electrode sheet in the prior art is solved, and the purpose of quickly screening out graphite materials with low OI value is achieved.
Patent Information
- Application Number
- CN202411878113.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-04
AI Technical Summary
The prior art is difficult to quickly and accurately determine the OI value of the water-based graphite negative electrode sheet, resulting in the inability to effectively screen out graphite materials with smaller OI values.
By directly testing the OI value of the oil-based negative electrode sheet with simple preparation method and short preparation period, instead of the OI value test of the water-based negative electrode sheet, the graphite material is screened based on the OI value of the oil-based negative electrode sheet.
It is possible to quickly and accurately obtain the OI value of the water-based graphite negative electrode sheet, and to quickly filter out graphite materials with low OI value or target OI value.
Smart Images

Figure BDA0005197455240000131 
Figure BDA0005197455240000141 
Figure BDA0005197455240000151
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials and relates to a method for obtaining the OI value of a water-based graphite negative electrode sheet and a method for screening graphite materials. Background Art
[0002] The OI value (orientation index) of graphite material is an important parameter to measure the degree of order of graphite layered structure, and the size of the OI value directly affects the performance of lithium-ion batteries. The smaller the OI value, the better the orientation of the graphite material, which is conducive to the diffusion of lithium ions inside the material, thereby improving the dynamic performance of the battery. Therefore, graphite materials with smaller OI values are usually used for battery preparation.
[0003] The OI value is usually measured by X-ray diffraction technology, specifically by analyzing the ratio of the peak intensity of the (004) crystal plane to the peak intensity of the (110) crystal plane in the graphite material. In the prior art, the OI value is usually calculated by directly measuring the XRD of the graphite material, but the OI value obtained by this method is unstable and has a large deviation, and it is impossible to accurately determine the size of the OI value of the graphite material, thereby failing to screen out the graphite material with the target OI value.
[0004] In the prior art, in order to improve the test accuracy, the OI value of the graphite material is also determined by testing the OI value of the all-electric negative electrode sheet prepared from graphite material. However, the all-electric negative electrode sheet is an aqueous all-electric negative electrode sheet, which has a long production cycle, a relatively complex process and a relatively high cost. It is impossible to quickly measure the OI value, and it is also impossible to quickly distinguish different graphite materials and achieve the purpose of screening graphite materials with smaller OI values.
[0005] Based on the above research, a method to quickly obtain the OI value of aqueous graphite negative electrode sheets is urgently needed. Summary of the invention
[0006] The object of the present invention is to provide a method for obtaining the OI value of a water-based graphite negative electrode sheet and a method for screening graphite materials. The present invention can directly test the OI value of an oil-based negative electrode sheet with a simple preparation method and a short preparation cycle, instead of testing the OI value of a water-based negative electrode sheet with a complex preparation method and a long cycle, and for different graphite materials, can quickly screen out graphite materials with lower OI values or other target OI values.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a method for obtaining an OI value of a water-based graphite negative electrode sheet, the method comprising the following steps:
[0009] The OI value of the oil-based graphite negative electrode sheet is tested, which is the OI value of the water-based graphite negative electrode sheet;
[0010] The compaction density of the oil-based graphite negative electrode sheet and the water-based graphite negative electrode sheet is the same, and the error is within ±5%, and the type of graphite material used in the oil-based graphite negative electrode sheet and the water-based graphite negative electrode sheet is the same;
[0011] The fineness of the oil-based coating slurry used to prepare the oil-based graphite negative electrode sheet is the same as the fineness of the water-based coating slurry used to prepare the water-based graphite negative electrode sheet, and the error is within ±5%; the particle size D50 of the oil-based coating slurry used to prepare the oil-based graphite negative electrode sheet is the same as the particle size D50 of the water-based coating slurry used to prepare the water-based graphite negative electrode sheet, and the error is within ±5%.
[0012] Preferably, the fineness of the oil-based coating slurry is 40±10 μm.
[0013] Preferably, in the oil-based coating slurry, the particle size D50 of the particles is 10±1 μm.
[0014] Preferably, the solid content of the oil-based coating slurry is 40-50wt%.
[0015] Preferably, the oil-based graphite negative electrode sheet and the water-based graphite negative electrode sheet are rolled or not rolled.
[0016] Preferably, the method for preparing the oil-based graphite negative electrode sheet comprises: coating the oil-based coating slurry on at least one side of the negative electrode current collector, and then drying it, and rolling it or not rolling it after drying.
[0017] Preferably, the oil-based coating slurry comprises a graphite material, an oil-based binder, a conductive agent and an oil-based solvent.
[0018] Preferably, the method for preparing the water-based graphite negative electrode sheet comprises: coating the water-based coating slurry on at least one side of the negative electrode current collector, and then drying it, and rolling it or not rolling it after drying.
[0019] Preferably, the water-based coating slurry comprises a graphite material, a water-based binder, a conductive agent and water.
[0020] Preferably, the method for testing the OI value of the oil-based graphite negative electrode sheet comprises performing an XRD test on the oil-based graphite negative electrode sheet to obtain I(004) and I(110), and calculating the OI value, wherein the OI value = I(004) / I(110).
[0021] In a second aspect, the present invention provides a method for screening graphite materials, the method comprising the following steps:
[0022] The graphite materials to be screened are respectively prepared into oil-based graphite negative electrode sheets, the OI values of the oil-based graphite negative electrode sheets are tested, and the target graphite materials are screened out according to the OI values of the oil-based graphite negative electrode sheets.
[0023] Preferably, the graphitization degree of the graphite material to be screened is above 85%, ensuring that the (110) plane of the graphite material used has a diffraction peak. If the graphitization degree is too low, the diffraction peak corresponding to the (110) crystal plane may not be detected, and it is not suitable for OI testing.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The present invention directly tests the OI value of an oil-based negative electrode sheet, which has a simple preparation method and a short preparation cycle, instead of testing the OI value of an aqueous negative electrode sheet. The OI value of the oil-based negative electrode sheet can directly reflect the OI value of the aqueous negative electrode sheet. The measured OI value of the oil-based graphite negative electrode sheet is the OI value of the aqueous graphite negative electrode sheet. Therefore, the OI value of the aqueous graphite negative electrode sheet can be quickly obtained. When a variety of graphite materials need to be screened, the graphite materials can be prepared into oil-based graphite negative electrode sheets for OI value testing, thereby enabling rapid screening of a variety of graphite materials. DETAILED DESCRIPTION
[0026] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0027] In a first specific implementation method, the present invention provides a method for obtaining the OI value of a water-based graphite negative electrode sheet, the method comprising the following steps:
[0028] The OI value of the oil-based graphite negative electrode sheet is tested, which is the OI value of the water-based graphite negative electrode sheet;
[0029] The compaction density of the oil-based graphite negative electrode sheet and the water-based graphite negative electrode sheet is the same, and the error is within ±5%, and the type of graphite material used in the oil-based graphite negative electrode sheet and the water-based graphite negative electrode sheet is the same;
[0030] The fineness of the oil-based coating slurry used to prepare the oil-based graphite negative electrode sheet is the same as the fineness of the water-based coating slurry used to prepare the water-based graphite negative electrode sheet, and the error is within ±5%; the particle size D50 of the oil-based coating slurry used to prepare the oil-based graphite negative electrode sheet is the same as the particle size D50 of the water-based coating slurry used to prepare the water-based graphite negative electrode sheet, and the error is within ±5%.
[0031] Since the result obtained by directly testing the OI value of graphite materials is inaccurate, the graphite materials can be prepared into aqueous graphite negative electrode sheets used in full batteries to test the OI value. The aqueous graphite negative electrode sheets are used as intermediate preparation materials between graphite materials and full batteries. Testing their OI values can, on the one hand, indirectly indicate the OI value of the graphite materials and, on the other hand, indicate the performance of the full battery. However, the preparation process of aqueous graphite negative electrode sheets is cumbersome and time-consuming, so it is impossible to quickly test and obtain their OI values.
[0032] In view of the above problems, the present invention directly tests the OI value of the oil-based negative electrode sheet, which has a simple preparation method and a short preparation cycle, instead of testing the OI value of the water-based negative electrode sheet. The OI value of the oil-based negative electrode sheet can directly reflect the OI value of the water-based negative electrode sheet. The measured OI value of the oil-based graphite negative electrode sheet is the OI value of the water-based graphite negative electrode sheet. Therefore, the method of the present invention can quickly obtain the OI value of the water-based graphite negative electrode sheet.
[0033] In addition, since the OI value of the electrode sheet is affected by the compaction density of the electrode sheet and the degree of dispersion and stability of the slurry when preparing the electrode sheet, it is necessary to ensure that the compaction density and the type of graphite material of the oil-based graphite negative electrode sheet and the water-based graphite negative electrode sheet are the same or similar, and the fineness of the slurry and / or the particle size D50 of the slurry are the same or similar (the error is within ±5%), so as to ensure that the OI value obtained by testing the oil-based graphite negative electrode sheet is the same or similar to the OI value obtained by testing the water-based graphite negative electrode sheet, thereby ensuring the reliability of the results.
[0034] The oil system in the oil-based graphite negative electrode sheet of the present invention refers to the oil-based binder and oil-based solvent used, and the water system in the water-based graphite negative electrode sheet refers to the water-based binder and solvent water used.
[0035] The compaction density of the oil-based graphite negative electrode sheet and the water-based graphite negative electrode sheet of the present invention is the same, and the error is within ±5%, which means that the compaction density of the oil-based graphite negative electrode sheet and the water-based graphite negative electrode sheet differs within ±5%, and is also considered to have the same compaction density, that is, the error of the same compaction density is allowed to be within ±5%, for example, it can be -5%, -4%, -3%, -2%, -1%, 0%, 1%, 2%, 3%, 4%, 0%, 1%, 2%, 3%, 4% or 5%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0036] The fineness of the oil-based coating slurry for preparing the oil-based graphite negative electrode sheet of the present invention is the same as the fineness of the water-based coating slurry for preparing the water-based graphite negative electrode sheet, and the error is within ±5%, which means that the fineness of the oil-based coating slurry and the water-based coating slurry differ within ±5%, and are also considered to have the same compaction density, that is, the error of the same fineness is allowed to be within ±5%, for example, it can be -5%, -4%, -3%, -2%, -1%, 0%, 1%, 2%, 3%, 4%, 0%, 1%, 2%, 3%, 4% or 5%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] The fineness of the slurry of the present invention is obtained by testing the slurry fineness using a scraper fineness meter. The test method is shown in the standard "GB / T 1724-2019".
[0038] The particle size D50 of the oil-based coating slurry for preparing the oil-based graphite negative electrode sheet of the present invention is the same as the particle size D50 of the water-based coating slurry for preparing the water-based graphite negative electrode sheet, and the error is within ±5%, which means that the particle size D50 of the oil-based coating slurry and the water-based coating slurry differs within ±5%, and is also considered to have the same particle size D50, that is, the error of the same particle size D50 is allowed to be within ±5%, for example, it can be -5%, -4%, -3%, -2%, -1%, 0%, 1%, 2%, 3%, 4%, 0%, 1%, 2%, 3%, 4% or 5%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0039] In some embodiments, the oil-based graphite negative electrode sheet and the water-based graphite negative electrode sheet use the same type of graphite material, and the particle size D50 of the graphite material used is also the same, and the error is within ±5%, which means that the particle size D50 of the oil-based coating slurry and the water-based coating slurry differs within ±5%, and is also considered to have the same particle size D50, that is, the error of the same particle size D50 is allowed to be within ±5%, for example, it can be -5%, -4%, -3%, -2%, -1%, 0%, 1%, 2%, 3%, 4%, 0%, 1%, 2%, 3%, 4% or 5%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0040] The particle size of the slurry of the present invention is tested by a particle size analysis laser diffraction method, see GB / T 19077-2024.
[0041] In some embodiments, the fineness of the oil-based coating slurry is 40±10μm, for example, it can be 30μm, 32μm, 34μm, 36μm, 38μm, 40μm, 42μm, 44μm, 46μm, 48μm or 50μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0042] In some embodiments, in the oil-based coating slurry, the particle size D50 of the particles is 10±1 μm, for example, it can be 9 μm, 9.2 μm, 9.4 μm, 9.6 μm, 9.8 μm, 10 μm, 10.2 μm, 10.4 μm, 10.6 μm, 10.8 μm or 11 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0043] The fineness of the oil-based coating slurry and the particle size of the particles of the present invention are within a certain range, so that the dispersion and stability of the slurry are basically equivalent to those of the existing water-based graphite negative electrode sheet slurry.
[0044] In some embodiments, the solid content of the oil-based coating slurry is 40-50wt%, for example, it can be 40wt%, 42wt%, 44wt%, 46wt%, 48wt% or 50wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0045] In some embodiments, the oil-based graphite negative electrode sheet and the water-based graphite negative electrode sheet are rolled or not rolled.
[0046] The electrode sheet of the present invention may be rolled or not, as long as the compaction density is the same. Since the OI values of the oil-based graphite negative electrode sheet and the water-based graphite negative electrode sheet before rolling are slightly different, in order to save cycles, it is preferred that the oil-based graphite negative electrode sheet and the water-based graphite negative electrode sheet are not rolled. However, if the OI value of the water-based graphite negative electrode sheet after rolling is to be obtained, the oil-based graphite negative electrode sheet and the water-based graphite negative electrode sheet need to be rolled. Therefore, those skilled in the art can choose according to needs.
[0047] In some embodiments, the method for preparing the oil-based graphite negative electrode sheet comprises: coating the oil-based coating slurry on at least one side of the negative electrode current collector, and then drying, and performing roll pressing or not performing roll pressing after drying.
[0048] In some embodiments, the oil-based coating slurry includes a graphite material, an oil-based binder, a conductive agent, and an oil-based solvent.
[0049] In some embodiments, in the oil-based coating slurry, the mass ratio of graphite material, oil-based binder and conductive agent is (90-96):(2-5):(0.5-1.5), for example, it can be 90:5:1.5, 92:2:0.5, 94:3:1 or 96:2:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0050] In some embodiments, the oil-based binder includes any one of polyvinylidene fluoride, polyimide, or polytetrafluoroethylene, or a combination of at least two thereof.
[0051] In some embodiments, the oil-based solvent includes N-methylpyrrolidone.
[0052] In some embodiments, the method for preparing the oil-based coating slurry comprises the following steps:
[0053] The oil-based solvent and the oil-based binder are mixed and dispersed, and then the conductive agent is added and continued to be mixed and dispersed, and then the graphite material and the oil-based solvent are added and continued to be mixed and dispersed.
[0054] In some embodiments, the method for preparing the water-based graphite negative electrode sheet includes: coating the water-based coating slurry on at least one side of the negative electrode current collector, and then drying, and rolling or not rolling after drying.
[0055] In some embodiments, the water-based coating slurry includes a graphite material, a water-based binder, a conductive agent, and water.
[0056] In some embodiments, in the water-based coating slurry, the mass ratio of graphite material, water-based binder and conductive agent is (90-96):(2-5):(0.5-1.5), for example, it can be 90:5:1.5, 92:2:0.5, 94:3:1 or 96:2:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0057] In some embodiments, the water-based binder includes any one of styrene-butadiene rubber, carboxymethyl cellulose, or polyvinyl alcohol, or a combination of at least two thereof.
[0058] In some embodiments, the conductive agent includes any one of carbon black, conductive graphite, carbon fiber, carbon nanotube or graphene, or a combination of at least two thereof.
[0059] In some embodiments, the graphite material (with a degree of graphitization of more than 85%) includes any one of single-particle or secondary-particle needle coke graphite material, petroleum coke graphite material, petroleum coke carbonized product or asphalt coke graphite material, or a combination of at least two thereof, wherein the petroleum coke graphite material is obtained by graphitizing petroleum coke, and the petroleum coke carbonized product is obtained by carbonizing the petroleum coke graphite material with asphalt coating.
[0060] In some embodiments, the method for testing the OI value of the oil-based graphite negative electrode sheet includes performing an XRD test on the oil-based graphite negative electrode sheet to obtain I(004) and I(110), and calculating the OI value, wherein the OI value = I(004) / I(110).
[0061] In a second specific implementation method, the present invention provides a method for screening graphite materials, the method comprising the following steps:
[0062] The graphite materials to be screened are respectively prepared into oil-based graphite negative electrode sheets, the OI values of the oil-based graphite negative electrode sheets are tested, and the target graphite materials are screened out according to the OI values of the oil-based graphite negative electrode sheets.
[0063] Since the OI value of the water-based graphite negative electrode sheet can reflect the OI value of the graphite material, the present invention can directly adopt an oil-based graphite negative electrode sheet with a simple preparation method and a short preparation cycle to replace the OI value test of the water-based graphite negative electrode sheet. When it is necessary to screen materials with lower OI values or target OI value ranges from a variety of graphite materials, the graphite materials to be screened can be prepared into oil-based graphite negative electrode sheets respectively, and the OI value of the oil-based graphite negative electrode sheet can be tested. Therefore, the target graphite material can be screened out according to the size of the OI value of the oil-based graphite negative electrode sheet.
[0064] In some embodiments, the degree of graphitization of the graphite material to be screened is above 85%, for example, it can be 85%, 87%, 89%, 91%, 93%, 95%, 97% or 99%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0065] The technical solution of the present invention is further illustrated by specific embodiments below.
[0066] The graphite materials used in the following examples and comparative examples include graphite AF, and the graphitization degree thereof is above 85%.
[0067] Graphite A is a secondary particle carbonized product obtained by carbonizing graphite B and asphalt;
[0068] Graphite B is a secondary particle graphitized product obtained by granulating petroleum coke raw material into secondary particles and then graphitizing them;
[0069] Graphite C is a single-particle carbonized product obtained by carbonizing graphite D and asphalt;
[0070] Graphite D is a single-particle graphitized product obtained by graphitizing petroleum coke;
[0071] Graphite E is a single-particle graphitized product obtained by graphitizing pitch coke;
[0072] Graphite F is a single-particle graphitized product obtained by graphitizing needle coke.
[0073] Example 1
[0074] This embodiment provides a method for obtaining the OI value of a water-based graphite negative electrode sheet. The method directly tests the OI value of an oil-based graphite negative electrode sheet, that is, the OI value of the water-based graphite negative electrode sheet. The method specifically includes the following steps:
[0075] (1) Preparation of oil-based graphite negative electrode sheet:
[0076] Prepare a mother solution according to the formula of NMP (N-methylpyrrolidone), PVDF (polyvinylidene fluoride) and SP (conductive carbon black) in a mass ratio of 50:3.67:1: first weigh a certain amount of NMP and PVDF and put them into a dispersion cup, stir them with a stirrer at a speed of 2000r / min for 20min, then weigh a corresponding amount of SP and add it to the above mixed solution, stir it with a stirrer at a speed of 2000r / min for 40min (no visible particles are seen when the dispersion cup is moved up and down) to obtain a mother solution;
[0077] The mother liquor was transferred to a stirring tank, and graphite C (the mass ratio of graphite C, PVDF and SP was 91.6:3.67:1) was added, and then a certain amount of NMP (to keep the solid content at 45wt%) was added, and the lid was closed and placed in a high-speed stirrer. The machine was turned on for revolution and rotation, and stirred at a low speed of 850r / min for 1min, and then stirred at a high speed of 2000r / min for 10min to obtain an oil-based coating slurry;
[0078] The fineness of the oil-based coating slurry is 40 μm, and the particle size D50 of the particles is 10 μm;
[0079] (2) Preparation of copper foil glass plate: First, sprinkle anhydrous ethanol on the center of the glass plate, then lay the copper foil flat on it with the fur side facing up, and then use dust-free paper to press in one direction so that the copper foil is tightly attached to the glass block without any bubbles remaining;
[0080] (3) Coating: Turn on the coater, and after initialization, place the glass plate with copper foil on the coater. Set the coating length and coating speed, where the coating speed is 30 mm / s. Place the glass plate to be coated on the coater, and buckle the scraper against the thrust rod on the glass plate. Use a spoon to check the uniformity of the slurry, put an appropriate amount of slurry on the scraper, and start the coater to start coating.
[0081] (4) Pole baking: Mark the coated glass plate and bake it in an oven for 2 hours at a temperature of 100°C. After cooling, the unpressed pole piece is obtained, which is marked as oil-cored electrode-unpressed, and is cut into pieces.
[0082] (5) Rolling: Continuously adjust the rolling pressure, roll the unpressed electrode sheet, weigh and measure the weight and thickness of the electrode sheet after rolling, so that the calculated compaction of the electrode sheet is 1.55g / cm 3 , and the compacted electrode is obtained, recorded as oil-based electrode -1.55.
[0083] (6) Test of OI value of graphite powder on the electrode: Take a glass sheet with a groove and fill the groove with plasticine until it is level with the upper surface of the glass sheet.
[0084] The electrode piece recorded as oil-based buckle-unpressed in step (4) and the electrode piece recorded as oil-based buckle-1.55 in step (5) are cut into electrode pieces of the same size as the groove, and the electrode pieces are placed on the plasticine. Then, a clean glass sheet is used to gently press down the entire electrode piece so that the electrode piece sticks to the plasticine.
[0085] Put the glass sheet with the electrode glued on it into the XRD diffraction instrument, the instrument model is Japan Rigaku SmartLab, remove the upper baffle of the instrument, set the test parameters to 0.02° step, 1.5° / min speed, 1 / 3 incident slit, and the test angle range is 53-56° and 76-79°, and start the test. Use jade software to fit the original spectrum after the test, read the peak intensity values of the 004 face and the 110 face respectively, calculate I(004) / I(110) and record it as the OI value, retain two decimal places.
[0086] Comparative Example 1
[0087] This comparative example provides a method for obtaining the OI value of a water-based graphite negative electrode sheet. The method directly tests the OI value of the water-based graphite negative electrode sheet, and specifically comprises the following steps:
[0088] (1) Prepare a water-based coating slurry according to the formula of graphite material, CMC (carboxymethyl cellulose), SBR (styrene-butadiene rubber) and SP at 95.5:1.5:2:1:
[0089] CMC glue solution preparation: weigh deionized water and CMC according to the concentration of 1.1% CMC glue solution, first pour 1 / 3 of deionized water into the stirring kettle of the double planetary mixer, then add CMC, and then slowly add the remaining deionized water to make it completely wet. Close the stirring kettle, stir at a revolution speed of 20rpm and a rotation speed of 1000rpm for 20min, scrape the material; then stir at a revolution speed of 45rpm and a rotation speed of 1800rpm for 120min to obtain CMC glue solution;
[0090] Conductive adhesive paste preparation: weigh SP according to the formula, slowly add it into CMC glue solution, close the stirring kettle, stir at an orbital speed of 20 rpm and an autorotation speed of 1000 rpm for 20 minutes, scrape the material; then stir at an orbital speed of 45 rpm and an autorotation speed of 1800 rpm for 120 minutes to obtain the conductive adhesive paste;
[0091] Adding graphite powder: weigh the graphite material (the same as in Example 1, graphite C) according to the formula, add it to the conductive adhesive paste, stir it for 20 minutes at a revolution speed of 20 rpm and a rotation speed of 1000 rpm, and scrape the material; then stir it for 60 minutes at a revolution speed of 45 rpm and a rotation speed of 1800 rpm, adjust the viscosity, and finally stir it for 60 minutes at a revolution speed of 45 rpm and a rotation speed of 1800 rpm;
[0092] Add SBR: weigh SBR according to the formula amount and add it to the slurry, stir at a revolution speed of 20 rpm and a rotation speed of 800 rpm for 30 minutes to obtain a water-based coating slurry with the same fineness and particle size D50 as Example 1;
[0093] (2) Preparation of copper foil glass plate: First, sprinkle anhydrous ethanol on the center of the glass plate, then lay the copper foil flat on it with the fur side facing up, and then use dust-free paper to press in one direction so that the copper foil is tightly attached to the glass block without any bubbles remaining;
[0094] (3) Coating: Turn on the coating machine and add appropriate amount of liquid slurry into the material tank. Test coat the electrode and conduct the first inspection of the electrode surface density, thickness and length. After the electrode parameters meet the requirements, single-sided coating is performed on the copper foil glass plate. After the single-sided coating is completed, continue the double-sided coating according to the single-sided coating process. Double-sided coating requires an additional coating alignment test;
[0095] (4) Cutting and slitting of electrodes: Start the slitting machine and put the large pieces to be cut in from the front. Be careful not to injure people when operating the equipment and putting in the electrodes. After the slitting is completed, weigh and mark the electrodes clearly and put them in the material tray. The unpressed electrodes are recorded as fully charged-unpressed;
[0096] (5) Pole sheet rolling: Continuously adjust the rolling pressure, roll the unpressed pole sheet, weigh and measure the weight and thickness of the pole sheet after rolling, so that the calculated compaction of the pole sheet is 1.55g / cm 3 , the compacted electrode is obtained, recorded as full power -1.55;
[0097] (6) Test of OI value of graphite powder on the electrode: Take a glass sheet with a groove and fill the groove with plasticine until it is level with the upper surface of the glass sheet;
[0098] The electrode piece recorded as fully powered-unpressed in step (4) and the electrode piece recorded as fully powered-1.55 in step (5) are cut into electrode pieces of the same size as the groove, and the electrode pieces are placed on the plasticine. Then, a clean glass sheet is used to gently press down the entire electrode piece so that the electrode piece sticks to the plasticine.
[0099] Put the glass sheet with the electrode glued on it into the XRD diffraction instrument, the instrument model is Japan Rigaku SmartLab, remove the upper baffle of the instrument, set the test parameters of step 0.02°, speed 1.5° / min, incident slit 1 / 3, test angle range 53-56° and 76-79°, and start the test. Use jade software to fit the original spectrum after the test, read the peak intensity values of 004 face and 110 face respectively, calculate I(004) / I(110) and record it as OI value.
[0100] The OI value test results of Example 1 and Comparative Example 1 are shown in Table 1:
[0101]
[0102]
[0103] Among them, the full-electric-unpressed in Table 1 is the electrode sheet of the water-based graphite negative electrode sheet prepared in Example 1 without rolling, and the full-electric-1.55 is the electrode sheet of the water-based graphite negative electrode sheet in Example 1 after rolling and the compaction density is 1.55g / cm 3 The electrode sheet of the oil-based graphite negative electrode sheet prepared in Example 1 is not rolled, and the oil-based graphite negative electrode sheet of Example 1 is rolled and has a compaction density of 1.55 g / cm 3 ; 1-1, 1-2 and 1-3 in Table 1 are three pole pieces with the same size as the groove cut from the same pole piece, 2-1, 2-2 and 2-3 refer to three pole pieces with the same size as the groove cut from the second batch of pole pieces prepared by the same method, 3-1, 3-2 and 3-3 refer to three pole pieces with the same size as the groove cut from the third batch of pole pieces prepared by the same method, 4-1, 4-2 and 4-3 refer to three pole pieces with the same size as the groove cut from the fourth batch of pole pieces prepared by the same method.
[0104] It can be seen from Table 1 that: (1) The OI value of the oil-based graphite negative electrode sheet that has not undergone the rolling process is close to the OI value data of the water-based graphite negative electrode sheet that has not undergone the rolling process, indicating that the direct test of the OI value of the oil-based negative electrode sheet, which has a simple preparation method and a short preparation cycle, can replace the OI value test of the water-based negative electrode sheet; (2) The OI values obtained by the electrode sheet that has not undergone the rolling process and the electrode sheet that has undergone the rolling process are different. Therefore, it is necessary to ensure that the oil-based graphite negative electrode sheet and the water-based graphite negative electrode sheet are consistent. The compaction density is the same; (3) The OI value results of the oil-based graphite negative electrode sheet and the water-based graphite negative electrode sheet that have not undergone the rolling process are the most stable, and the results of the two are very similar; (3) The OI value results of the oil-based graphite negative electrode sheet and the water-based graphite negative electrode sheet that have undergone the rolling process increased significantly and the stability became worse, but the results were still similar. From the above conclusions, it can be seen that the electrode OI value test is stable, and the OI value of the oil-based graphite negative electrode sheet can replace the characterization of the OI value of the water-based graphite negative electrode.
[0105] Example 2
[0106] This embodiment provides a method for screening graphite materials, the method comprising the following steps:
[0107] The graphite materials to be screened were prepared into oil-based graphite negative electrode sheets by the method of Example 1. The oil-based graphite negative electrode sheets that were not rolled were marked as oil-unrolled. 3 The roller pressure is recorded as oil system -1.55 pressure, and then the OI value is tested using the method in Example 1.
[0108] Comparative Example 2
[0109] This comparative example provides a method for screening graphite materials, the method comprising the following steps:
[0110] The graphite materials to be screened were prepared into water-based graphite negative electrode sheets by the method of comparative example 1. The water-based graphite negative electrode sheets were not rolled and recorded as full-electric-unrolled. 3 The roller pressure is recorded as full electric -1.55 pressure, and then the OI value is tested by the method in Comparative Example 1.
[0111] The test results of Example 2 and Comparative Example 2 are shown in Table 2:
[0112] Table 2
[0113]
[0114]
[0115] It can be seen from Table 2 that different types of graphite materials have different OI values. The OI values of the electrodes increase significantly after rolling. The OI value of the oil-based graphite negative electrode sheet is similar to that of the water-based graphite negative electrode sheet, which once again shows that the OI value of the oil-based graphite negative electrode sheet can replace the OI value of the all-electric water-based graphite negative electrode sheet.
[0116] In summary, the present invention provides a method for obtaining the OI value of a water-based graphite negative electrode sheet and a method for screening graphite materials. The present invention can directly test the OI value of an oil-based negative electrode sheet with a simple preparation method and a short preparation cycle, instead of testing the OI value of a water-based negative electrode sheet with a complex preparation method and a long cycle, and for different graphite materials, can quickly screen out graphite materials with lower OI values or other target OI values.
[0117] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A method for obtaining the OI value of a water-based graphite negative electrode sheet, characterized in that: The method comprises the following steps: The OI value of the oil-based graphite negative electrode sheet is tested, which is the OI value of the water-based graphite negative electrode sheet; The compaction density of the oil-based graphite negative electrode sheet and the water-based graphite negative electrode sheet is the same, and the error is within ±5%, and the type of graphite material used in the oil-based graphite negative electrode sheet and the water-based graphite negative electrode sheet is the same; The fineness of the oil-based coating slurry used to prepare the oil-based graphite negative electrode sheet is the same as the fineness of the water-based coating slurry used to prepare the water-based graphite negative electrode sheet, and the error is within ±5%; the particle size D50 of the oil-based coating slurry used to prepare the oil-based graphite negative electrode sheet is the same as the particle size D50 of the water-based coating slurry used to prepare the water-based graphite negative electrode sheet, and the error is within ±5%.
2. The method according to claim 1, characterized in that The fineness of the oil-based coating slurry is 40±10 μm; Preferably, in the oil-based coating slurry, the particle size D50 of the particles is 10±1 μm; Preferably, the solid content of the oil-based coating slurry is 40-50wt%.
3. The method according to claim 1 or 2, characterized in that: The oil-based graphite negative electrode sheet and the water-based graphite negative electrode sheet are rolled or not rolled.
4. The method according to any one of claims 1 to 3, characterized in that: The method for preparing the oil-based graphite negative electrode sheet comprises: coating the oil-based coating slurry on at least one side of the negative electrode current collector, and then drying it, and rolling it or not rolling it after drying.
5. The method according to any one of claims 1 to 4, characterized in that: The oil-based coating slurry comprises a graphite material, an oil-based binder, a conductive agent and an oil-based solvent.
6. The method according to any one of claims 1 to 5, characterized in that: The method for preparing the water-based graphite negative electrode sheet comprises: coating the water-based coating slurry on at least one side of the negative electrode current collector, and then drying it, and rolling it or not rolling it after drying.
7. The method according to any one of claims 1 to 6, characterized in that: The water-based coating slurry comprises a graphite material, a water-based binder, a conductive agent and water.
8. The method according to any one of claims 1 to 7, characterized in that: The method for testing the OI value of the oil-based graphite negative electrode sheet includes performing an XRD test on the oil-based graphite negative electrode sheet to obtain I(004) and I(110), and calculating the OI value, wherein the OI value = I(004) / I(110).
9. A method for screening graphite materials, characterized in that: The method comprises the following steps: The graphite materials to be screened are respectively prepared into oil-based graphite negative electrode sheets, the OI values of the oil-based graphite negative electrode sheets are tested, and the target graphite materials are screened out according to the OI values of the oil-based graphite negative electrode sheets.
10. The method according to claim 9, characterized in that The graphitization degree of the graphite material to be screened is above 85%.